Perceptions of sexual harassment and drivers of reporting in two higher learning institutions in Bulawayo, Zimbabwe - Dube, Thulani; Ncube, Siphilisiwe B; Mlotshwa, Simon (Penerbit Universiti Kebangsaan Malaysia, 2021)
Sexual harassment in institutions of higher learning is recognized as a violation of the right to life, liberty and equality for women. This study investigated the knowledge and perceptions of sexual harassment by female students in two higher learning institutions in Bulawayo. The study assessed the understanding of the concept of sexual harassment, the experiences of female students with sexual harassment, and how they respond to sexual harassment offences perpetrated against them. The study also focused on the drivers of reporting amongst victims of sexual harassment at the targeted institutions. The study adopted a mixed methods approach in data collection involving a structured survey questionnaire, key informant interviews and focus group discussions targeting both male and female students in the targeted study sites. The study established that female students are more likely to experience sexual harassment than male students. The study also established that the definition of the concept of sexual harassment was often problematic for uninformed victims. This, and other factors led to low levels of reporting of sexual harassment and the continued perpetration of this vice. We recommend a raft of measures to address emerging issues from this research.